2023
DOI: 10.1177/03611981221151073
|View full text |Cite
|
Sign up to set email alerts
|

Linking Police and EMS Records: An Approach to Strengthen Bicyclist Injury Reporting

Abstract: Bicyclist injuries are underreported in police crash databases. We explored the value of linking police-reported crash data with emergency medical services (EMS) data within the City of Milwaukee, WI. Using data from 2014 to 2016, we linked records by inspection (identical date, similar time of day, and similar roadway location) and found 154 matching records between the two databases (representing 41% of the 375 police crash records and 44% of the 348 EMS injury records). Matched records were more likely to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Next, we calculated sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for the manually reviewed dataset to the injury cause codes and for the manually reviewed dataset to the ED visit data. We specifically chose to examine EMS data because precedence [7][8][9][10][11] has shown that EMS narratives can provide rich contextual details on the entire EMS encounter; therefore, the EMS data should provide insights into firearm injury intent.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we calculated sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for the manually reviewed dataset to the injury cause codes and for the manually reviewed dataset to the ED visit data. We specifically chose to examine EMS data because precedence [7][8][9][10][11] has shown that EMS narratives can provide rich contextual details on the entire EMS encounter; therefore, the EMS data should provide insights into firearm injury intent.…”
Section: Introductionmentioning
confidence: 99%